2022
DOI: 10.3390/toxins14050339
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Rotenone and Deguelin Contents among Strains across Four Tephrosia Species and Their Activities against Aphids and Whiteflies

Abstract: Botanical pesticides have received increasing attention for sustainable control of insect pests. Plants from the genus Tephrosia are known to produce rotenone and deguelin. Rotenone is known to possess insecticidal activities against a wide range of pests, but deguelin’s activities remain largely inconclusive. On the other hand, the biosynthesis of rotenone and deguelin may vary in Tephrosia species. This study analyzed the rotenone and deguelin contents in 13 strains across 4 Tephrosia species over 4 growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Additionally, rotenone exhibits anticancer activity in vitro but its application is limited due to neurotoxicity associated with its ability to cross the blood-brain barrier (Cannon et al, 2009;Deng et al, 2010). However, hydroxylated rotenoids are more hydrophilic and less likely to readily cross the blood-brain barrier, potentially acting as cellselective killers to inhibit the proliferation of cancer cells (Naguib et al, 2018;Zhang et al, 2022a). Indeed, the diversity and complexity of isoflavonoid compounds are largely due to chemical modifications such as methylation, glycosylation, and acylation.…”
Section: Figurementioning
confidence: 99%
“…Additionally, rotenone exhibits anticancer activity in vitro but its application is limited due to neurotoxicity associated with its ability to cross the blood-brain barrier (Cannon et al, 2009;Deng et al, 2010). However, hydroxylated rotenoids are more hydrophilic and less likely to readily cross the blood-brain barrier, potentially acting as cellselective killers to inhibit the proliferation of cancer cells (Naguib et al, 2018;Zhang et al, 2022a). Indeed, the diversity and complexity of isoflavonoid compounds are largely due to chemical modifications such as methylation, glycosylation, and acylation.…”
Section: Figurementioning
confidence: 99%
“…or Mundulea sericea (Leguminosae). 48 Rotenone, a highly toxic deguelin-analogue, has traditionally served as an insecticide and a herbicide for an extended period of time, 49 and has been studied as an inducer of Parkinson's disease. 50,51 Despite their structural similarities to rotenone, several studies have reported that deguelin exhibits distinct aspects of toxicity and molecular function compared to rotenone.…”
Section: Introductionmentioning
confidence: 99%
“…Deguelin (Figure 1) is a naturally occurring rotenoid 1 that was originally used as pesticide and fish poison. 2 It has emerged as a promising lead compound for therapeutic optimization and development due to its remarkable antiproliferative activity and unique mechanism of action. 3 Its favorable biological activity has been attributed to its role in regulating various tumor cell signaling transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Deguelin (Figure ) is a naturally occurring rotenoid that was originally used as pesticide and fish poison . It has emerged as a promising lead compound for therapeutic optimization and development due to its remarkable antiproliferative activity and unique mechanism of action .…”
Section: Introductionmentioning
confidence: 99%